Utilization of Library Collections to Meet User Needs In The Diplomacy Library - Rahmadhan, Mutiara (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
Libraries are organizations that provide information services, and should emphasize assessing the number of users served and the level of satisfaction. The library is a scientific institution that has main tasks related to science, education, research and development, with its scope of managing and storing information covering various sciences and technology. Utilization of collections in the Library Diplomacy is a way to utilize collections by filling out guest books, borrowing collections from the library, and reading in the library. The needs of users in utilizing important library collections to provide relevant and meaningful services. Provides a diverse collection to cover a wide range of interests, knowledge levels, and educational needs. Influences interest in visiting the library, both external and internal influences. This research is entitled "Utilization of Library Collections in Meeting the Needs of Readers in the Diplomacy Library". The aim of this research is to see the use of library collections in meeting the needs of users. Quantitative research methods are methods used to explain phenomena using numerical data, followed by analysis which usually uses statistics. Using data collection techniques using questionnaires or questionnaires which were given to each respondent personally. The results obtained from this research are the use of library collections to meet the needs of users effectively and efficiently for use by users because library materials are a source of knowledge owned by the library. The importance of physical interaction with collections, creating direct and immersive experiences in research or study. Apart from that, there are still other influences such as internal and external influences around him.